PENGALAMAN BERAGAMA SUFI JALALUDDIN RUMI DALAM PERSPEKTIF PSIKOLOGI - Hajriansyah Hajriansyah (Jurnal Ilmiah Ilmu Ushuluddin, 2015)
Sufis poetry or the poetry of Islamic Mysticism is part of the cultural heritage of Islam. If the mention of the manynames of Sufi poets, the most commonly known and easily referred to is the name of Maulana Jalaluddin Rumi orRumi. This writing wants to frame the religious experience of Rumi, through his poetries that reflects the attitude ofSufis doctrine, in the perspective of Sufi psychologhy. The conclusion was obtained that Rumi was from the type ofprophetic religion, so that his attitude of the religion did not leave Syariat aspects which part of Islamic doctrine,although he put a lot of mystical attitude in his eccentric poems since his meeting with Syams Tabriz.